2010
DOI: 10.1002/fuce.200900141
|View full text |Cite
|
Sign up to set email alerts
|

Gas Diffusion Layers for Proton Exchange Membrane Fuel Cells Using In situ Modified Carbon Papers with Multi‐walled Carbon Nanotubes Nanoforest

Abstract: Gas diffusion layers (GDLs) in the proton exchange membrane fuel cells (PEMFCs) enable the distribution of reactant gases to the reaction zone in the catalyst layers by controlling the water in the pore channels apart from providing electrical and mechanical support to the membrane electrode assembly (MEA). In the present work, we report the in situ growth of carbon nanotubes nanoforest (CNN) directly onto macro‐porous carbon paper substrates. The surface property as analysed by a Goniometer showed that the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…26 An in situ grown CNN/carbon paper working as the gas diffusion layer was reported to have excellent performance in the PEMFC. 27 Novel GDL for PEMFCs was prepared by in situ growing Pt nanowires on carbon paper. 28 Pt/SC-CNFs (stackedcup carbon nano fiber) was used to produce a CCM, the better mass transport attributed to a thinner anode catalyst layer led to overall PEMFC performance improvement.…”
Section: Resultsmentioning
confidence: 99%
“…26 An in situ grown CNN/carbon paper working as the gas diffusion layer was reported to have excellent performance in the PEMFC. 27 Novel GDL for PEMFCs was prepared by in situ growing Pt nanowires on carbon paper. 28 Pt/SC-CNFs (stackedcup carbon nano fiber) was used to produce a CCM, the better mass transport attributed to a thinner anode catalyst layer led to overall PEMFC performance improvement.…”
Section: Resultsmentioning
confidence: 99%
“…6) leading to performance improvement (power density) by 10%, using oxygen or air on the cathode side (at ambient pressure and 70 o C) due to a better electrical conductivity and large surface area of the MWCNTs. The authors [13] also showed that due to hydrophobic nature of the MWCNTs the Nanoforest-based GDLs can operate in lower humidity up to 30% producing up to 70% improvement in the operation of the PEM fuel cells at lower humidity employing conventional GDLs. Also, since the GDLs do not absorb moisture, they will have extended lifetime.…”
Section: B Gas Diffusion Layersmentioning
confidence: 97%
“…While GNSs are primary used for the performance enhancement of the resin system called Nanoresin [1]- [3], CNT Nanoforests and nanofilms [4]- [9] are used to improve the performance of fiber systems in high-performance Nanocomposites. Next, the use of CNTs as gas diffusion layers and CNTs combined with in-situ generated platinum nanoparticles as catalyst layers to improve the performance, efficiency, and durability of proton exchange membrane fuel cells while reducing their costs, weight, and size will be reviewed [9]- [13]. In addition, the use of CNTs and GNSs to improve the efficiency and performance of polymer solar cells will be reviewed [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The wetting of nanotube forests and arrays has been investigated with several liquids including water, glycerol, ethylene glycol, propylene carbonate, olive oil, dimethyl sulfoxide, and nitromethane with contact angles ranging between 60 and 157° [33]. CNT forests have been used to grow hematite nanochain arrays, as filters to capture micro/nanocontaminants in water, and as gas diffusion arrays with contact angles up to 150° [34].…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%